Comparative Intracellular Cytokine Production by In Vitro Stimulated T Lymphocytes from Human Umbilical Cord Blood (HUCB) and Adult Peripheral Blood (APB) - J. A. García Vela; I. Delgado; R. Bornstein; B. Alvarez; M. C. Auray; I. Martin; F. Oña; F. Gilsanz (Analytical Cellular Pathology)
To date over 400 HUCB transplants have been reported from different centers. It has been suggested that there is a reduced graft‐versus‐host‐disease (GVHD) with HUCB compared to bone marrow transplantation. Since cytokine production by a cell is an indication of the cells function it is important to determinate the differences between APB and HUCB with respect to production of these soluble factors. Our aim was to analyse the intracellular cytokine production by HUCB and APB T lymphocytes with and emphasize on their possible role in GVHD.